Influence of cutting fluid on machining processes : a review - Araoyinbo, Alaba Oladeji; Edun, Mosunmola Bose; Samuel, Ayuba Ushe; Azmi Rahmat; Biodun, Matthew Biola; Mohammed Mustafa Albakri (Penerbit Universiti Kebangsaan Malaysia, 2022)
Machining process in Manufacturing system is the removal of material to produce a desired shape, size and, or weight of a particular part. This involves the use of cutting, grinding and boring tools as the case maybe, the process itself is not free from challenges that includes reduction in tool life which are usually affected and also the effect of friction which affects machine parts. Therefore, an engineering practice in manufacturing system is required to eliminate or bring to bare minimum the challenges in this machining processes, hence the cutting fluid technology is researched to be a solution solving process. Cutting fluids are widely used and has been majorly seen as a necessary additive to enhance output and increased quality machining operations. The effect of friction leads to sudden rise in cutting temperature and tool wear during machining which impair the quality of the final product. The highly recognized cooling techniques utilized between the several cooling techniques used in metalworking are nanofluids, cryogenic systems, and cooled trodden air. The utilization of cutting fluids cannot be overlooked during machining process as it forms strong defensive films in the contact territories at low speed, making the grip frailer and averting the creation of stores, hence, lowering friction between two mating parts. The resultant effect of good cutting fluid during machining operation enhanced good surface roughness and better service life of the device and suitable finished surface of workpiece that are subjected to machining operations.